2008
DOI: 10.1016/j.physa.2008.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Some extensions of the uncertainty principle

Abstract: We study the formulation of the uncertainty principle in quantum mechanics in terms of entropic inequalities, extending results recently derived by BialynickiBirula [1] and Zozor et al. [2]. Those inequalities can be considered as generalizations of the Heisenberg uncertainty principle, since they measure the mutual uncertainty of a wave function and its Fourier transform through their associated Rényi entropies with conjugated indices. We consider here the general case where the entropic indices are not conju… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
96
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(104 citation statements)
references
References 18 publications
7
96
0
1
Order By: Relevance
“…Finally, let us also mention that Zozor et al [20] showed that for β > α * no uncertainty principle exists, in the sense that the product of Rényi entropy powers is just trivially non-negative. But below the conjugation curve, it is not known yet neither the sharpest bound, nor the states that saturate the uncertainty relation.…”
Section: Entropic Uncertainty Relations: a Brief Reviewmentioning
confidence: 98%
“…Finally, let us also mention that Zozor et al [20] showed that for β > α * no uncertainty principle exists, in the sense that the product of Rényi entropy powers is just trivially non-negative. But below the conjugation curve, it is not known yet neither the sharpest bound, nor the states that saturate the uncertainty relation.…”
Section: Entropic Uncertainty Relations: a Brief Reviewmentioning
confidence: 98%
“…In this work we are not interested in the precise lower bounds of q , q , or U q [9]. Instead we are worried by contradictions between the conclusions derived from different choices of q.…”
Section: Joint Uncertaintiesmentioning
confidence: 99%
“…These measures may enter in uncertainty relations for two observables A,B via nontrivial lower bounds on different combinations [4][5][6][7][8][9], such as the sum of Tsallis entropies…”
Section: Joint Uncertaintiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Generalized entropies have also found use as alternate measures of an informational content. For instance, the entropic uncertainty principle has been expressed in terms of both the Tsallis [27,35] and Rényi entropies [38,48]. Studies of generalized entropies allow to treat properties of the standard entropy in more general setting.…”
Section: Introductionmentioning
confidence: 99%